Kedudukan Hukum Hasil Rapat Anggota Tahunan Sebagai Dasar Dalam Menjalankan Kegiatan Usaha Koperasi (Studi Pada Kantor Koperasi Karya Bahari Lombok Utara) - M Mulyawan (Jurnal Ilmiah Penegakan Hukum, 2023)
This study aims to determine the legal standing of the results of the Annual Member Meeting as a basis for carrying out cooperative business activities (study at the Karya Bahari Cooperative Office, North Lombok) ". This research is a kind of juridical-empirical research. The empirical study in this study was carried out through field studies by collecting primary data from respondents in the Karya Bahari Cooperative, North Lombok Regency. The juridical study in this research was carried out through a literature study by collecting secondary data in the form of laws and regulations relating to the protection of cooperative administrators. The results of the research show that as regulated in Law Number 25 of 1992 concerning Cooperatives in Article 22 Paragraph (1) which reads: "Members' Meetings are the highest authority in cooperatives" The law has regulated these interests. However, even though the law already exists, these companies often violate it to the point of causing harm to both the wider community and other companies. In Law No. 25 of 1992 concerning Cooperatives, and the Articles of Association of the Karya Bahari Cooperative "Navy" of North Lombok Regency, it does not specifically regulate legal protection for Cooperative Management. Thus, preventive legal protection is very significant for government actions based on freedom of action because with preventive legal protection, cooperative managers are encouraged to be careful in making decisions based on law. The handling of legal protection in general courts in Indonesia is included in the category of repressive legal protection